General configuration of automation system within a high voltage power substation - Trabulus, S (IEEE, 2000)
The need to provide quick, accurate and prioritized power system information can take a significant toll on electric power utilities' resources, challenging their ability to remain competitive. The Substation Automation Systems will help satisfy these needs, reducing operation and maintenance costs, while maximizing the total return on investment. In this paper the main units such as Hardware, Software, Remote Control, Networks and Monitoring, which create the general configuration of Automation System in a high voltage power substation, are discussed with the newest technological designs.
Keywords: Engineering